Key to Chinese species of Copidosoma (Hymenoptera: Encyrtidae), with new records and three new species - Wang, Hai-Yan; Li, Cheng-De (Zootaxa, 2018)
Six species of Copidosoma (Hymenoptera: Encyrtidae) from Southwestern China are reviewed, including three new species (C. heinitane sp. nov., C. linzhiensis sp. nov., C. longchuane sp. nov.) and two species newly recorded from China (C. longiclavatum Kazmi & Hayat and C. recurvariae Sharkov). Copidosoma serricorne (Dalman) is newly recorded from Xizang, southwestern part of China. A key to all the Chinese species of the genus based on females is given.